Development of a high temperature facility for study of aerosol emission behavior of combustible materials - Yadav S.K.; Khan A.; Shukla P. (My University, 2025)
Aerosol size and number/mass size distribution are vital parameters for evaluating their effect on human health and the environment. To study the aerosol emission behavior of a material, a high temperature facility has been designed. Combustible materials like biomass, wood, agricultural residue as well as commercially used material like graphite can be burnt and characterized using this facility. In the present work, nuclear grade graphite has been tested in the facility, which can attain a maximum furnace temperature of 1350 °C with an air flow rate of 25 lpm. A cooling and dilution mechanism was incorporated to lower the temperature of the aerosol-laden gas to the desired value for aerosol size measurement using spectrometers. Isokinetic sampling has been ensured using a specially designed probe. Losses due to thermophoresis, condensation and coagulation, etc. have also been calculated and are found to less than 5%. © 2019 Elsevier Ltd